OP08 Expression of the immune checkpoints CD96 and CD226 on ascitic immune cells in patients with decompensated liver disease denotes a more immunosuppressive phenotype. (20th September 2022) - Delo, Joseph; Forton, Daniel; Triantafyllou, Evangelos; Singanayagam, Arjuna
Abstract : Background: Decompensated cirrhosis is associated with a marked susceptibility to infection with spontaneous bacterial peritonitis being one of the most common infections. Non-cirrhotic ascites rarely becomes infected so the degree and mechanism of immune-paresis in the ascitic immune environment is of particular interest. Immune checkpoints constitute a complex array of regulatory receptors and ligands expressed on the surface of immune cells. They serve as pivotal regulators of the host immunity and so we hypothesise they may be involved in immune dysfunction in the ascitic immune environment. CD96 and TIGIT are inhibitory receptors expressed on T cells and NK cells that are thought to exert immunosuppressive effects by outcompeting CD226, a co-stimulatory receptor also expressed on T cells and NK cells, for binding of its ligand CD155 on antigen presenting cells. Methods: Patients with decompensated cirrhosis were recruited from the inpatient ward and healthy volunteers recruited as controls. Blood samples were collected for isolation of peripheral blood mononuclear cells (PBMC), and ascites mononuclear cells were obtained by centrifugation of ascitic fluid. Cell surface expression of the immune checkpoints CD96, TIGIT, and CD226 on T cells and NK cells, and their ligand CD155 on monocytes/macrophages was determined with flow cytometry analysis. Healthy control PBMCs were cultured with TLR ligands and expression of CD155 on monocytes determined with flow cytometry analysis. Results: A significantly higher percentage of ascitic CD8+ T cells and NK cells were CD96+ compared to paired peripheral cells from the same patient, whereas a significantly lower percentage were CD226+. There was a trend of higher CD155 expression on ascitic macrophages compared to peripheral monocytes. Healthy control monocyte expression of CD155 was significantly increased by TLR4 stimulation with the bacterial component lipopolysaccharide. Expression of these immune checkpoints on ascitic immune cells did not significantly change with severity of liver disease from stable decompensation, acute decompensation and acute-on-chronic liver failure. Discussion: The CD96, CD226 and CD155 expression on ascitic immune cells in decompensated cirrhosis is of a more immunosuppressive phenotype compared to corresponding peripheral immune cells. This may in part be explained by chronic background exposure to translocated bacterial products in the ascites and may pre-dispose to SBP.